Skin care of premature newborns: integrative review - Natália Del Angelo Aredes; Raionara Cristina de Araújo Santos; Luciana Mara Monti Fonseca (Universidade Federal de Goias, 2017)
To describe and analyze scientific evidence in national and international studies on nursing care for skin integrity of preterm newborns (PTNBs) in the Neonatal Intensive Care Unit (NICU). Integrative review in LILACS, BDENF, SciELO, CINAHL, PubMed and EMBASE. Twenty-three articles that met the inclusion criteria were selected with use of the PRISMA method. Ten studies addressed products for the skin of preterm infants; five focused on bathing and diaper dermatitis; two reported use of incubators and control of transepidermal water loss; two discussed pressure injuries; and four addressed the protocols and practices of nurses in skin care. The results showed there are many products available, but a lack of evidence for their practical application. Bath products and periodicity and care for pressure injuries were better addressed in the literature, in spite of gaps in the prevention of infections and injuries, and use of protocols.